1995
DOI: 10.1104/pp.107.2.315
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Toxicity and Tolerance in Plants

Abstract: Aluminum (Al) is the most abundant metal in the earths crust, comprising about 7% of its mass. Since many plant species are sensitive to micromolar concentrations of Al, the potential for soils to be A1 toxic is considerable. Fortunately, most of the A1 is bound by ligands or occurs in other nonphytotoxic forms such as aluminosilicates and precipitates. However, solubilization of this A1 is enhanced by low pH and A1 toxicity is a major factor limiting plant production on acid soils. Soil acidification can deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
624
1
24

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,133 publications
(687 citation statements)
references
References 27 publications
15
624
1
24
Order By: Relevance
“…However, no indication of internal detoxification (Ma et al 2001) was observed. Therefore, aluminium tolerance per se in tolerant genotypes of pigeonpea involved aluminium exclusion (Delhaize and Ryan 1995;Kochian 1995).…”
Section: Hydroponic Assay: Nutrient Uptake Behaviourmentioning
confidence: 99%
“…However, no indication of internal detoxification (Ma et al 2001) was observed. Therefore, aluminium tolerance per se in tolerant genotypes of pigeonpea involved aluminium exclusion (Delhaize and Ryan 1995;Kochian 1995).…”
Section: Hydroponic Assay: Nutrient Uptake Behaviourmentioning
confidence: 99%
“…O cultivo em solução nutritiva é de grande interesse para a seleção de plantas ou em estudos especí-ficos de fisiologia e nutrição, graças à facilidade que esse método oferece na avaliação da parte aérea e do sistema radicular (Delhaize & Ryan, 1995). Além de permitir melhor controle das variáveis não experimentais, o que aumenta a precisão dos testes (Spehar, (1) Aceito para publicação em 2 …”
Section: Soybean Genotypes Reaction To Aluminium In Hydroponics and Soilunclassified
“…Root growth inhibition, reduction in water absorption and nutrient uptake (Delhaize & Ryan 1995), ROS production and lipid peroxidation (Cakmak & Horst 1991) are characteristic responses to Al stress. Even very low Al levels may cause signifi cant metabolic responses in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Due these aspects, Al toxicity is becoming an economically important issue, because acid soil comprise up 70% of the world's arable lands, limiting the growth of important food crops and causing severe food losses (Kochian et al 2002, Chen et al 2010. The major recognised symptom of Al toxicity is the inhibition of root growth, but it can also provoke a reduction in respiration and ATP synthesis (Delhaize & Ryan 1995, Yamamoto et al 2003.…”
Section: Introductionmentioning
confidence: 99%